1994
DOI: 10.1021/ie00026a007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodesulfurization reactivities of various sulfur compounds in diesel fuel

Abstract: The hydrodesulfurization (HDS) of a diesel oil was carried out in a batch autoclave reactor over the temperature range 280-420 °C for 0-90 min under a total pressure of 2.9 MPa, using CoMo and NiMo catalysts in both one and two stages. The HDS reactivities of benzothiophenes, dibenzothiophenes (DBTs), and their alkylated homologes existing in the diesel fuel were examined in detail by means of respective quantitative analyses. The sulfur compounds can be classified into four groups according to their HDS react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
224
2
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 433 publications
(245 citation statements)
references
References 11 publications
12
224
2
7
Order By: Relevance
“…The majority of sulfur-containing hydrocarbons in liquid fuels are converted to sulfur-free compounds and H 2 S by catalytic hydrodesulphurization (HDS) reactions during the fuel processing. Although the HDS process is the best known technology for desulfurization of liquid fuels, it cannot efficiently remove thiophenic compounds (TC) including dibenzothiophene (DBT), 4,6-dimethyldibenzothiophene (4,6-DMDBT), and benzothiophene (BT) to meet the new environmental regulations of 15-30 ppm sulfur in the processed fuels [1][2][3][4][5]. Reactivity studies of BT, DBT and their alkylated homologues in HDS reactions over Co, Mo/Al 2 O 3 , Ni, Mo/Al 2 O 3 and sulfide Co, Mo/γ-Al 2 O 3 catalysts indicate that the alkyl group substituents, especially in positions subject to steric hindrance effects (e.g., 4 and 6 in the 4,6-DMDBT molecule) significantly reduce the reactivity of TC in HDS reactions [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of sulfur-containing hydrocarbons in liquid fuels are converted to sulfur-free compounds and H 2 S by catalytic hydrodesulphurization (HDS) reactions during the fuel processing. Although the HDS process is the best known technology for desulfurization of liquid fuels, it cannot efficiently remove thiophenic compounds (TC) including dibenzothiophene (DBT), 4,6-dimethyldibenzothiophene (4,6-DMDBT), and benzothiophene (BT) to meet the new environmental regulations of 15-30 ppm sulfur in the processed fuels [1][2][3][4][5]. Reactivity studies of BT, DBT and their alkylated homologues in HDS reactions over Co, Mo/Al 2 O 3 , Ni, Mo/Al 2 O 3 and sulfide Co, Mo/γ-Al 2 O 3 catalysts indicate that the alkyl group substituents, especially in positions subject to steric hindrance effects (e.g., 4 and 6 in the 4,6-DMDBT molecule) significantly reduce the reactivity of TC in HDS reactions [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the sulfur components in the fuels is based on a combination of various techniques, including HPLC, sulfur-selective ligand exchange chromatography (Ma et al, 1997), GC-MS (Ma et al, 1994(Ma et al, , 1997, retention time comparison with literature data (Depauw and Froment, 1997;Chawla and Sanzo, 1992) HDS reactivities of various sulfur compounds (Ma et al, 1994;] and understanding of the elution order of the isomers (Lai and Song, 1995).…”
Section: Sample Analysismentioning
confidence: 99%
“…It was observed that the overall kinetics for the HDS of these species could be described by lumping the rate constants for the individual sulfur species into four reactivity groups [60][61][62][63][64]. These groups, listed in order of decreasing reactivity, are as follows:…”
Section: Reactivity Of Poly Aromatic Sulfur Compoundsmentioning
confidence: 99%